Dwell-time-dependent asynchronous mixed H∞ and passive control for discrete-time switched systems. (May 2022) - Zhang, Siyuan; Nie, Hong
Abstract: This paper investigates the asynchronous mixed H ∞ and passivity-based control problem for discrete-time switched systems obeying dwell time constraint. Based on the improved dwell-time-dependent Lyapunov function, a novel combined switching mechanism made up of the time-dependent and state-dependent switching strategies is constructed to ensure the resultant systems with asynchronous switching to be asymptotically stable and achieve a weighted mixed H ∞ and passivity performance. Meanwhile, asynchronous weighted mixed H ∞ and passivity-based controllers are designed in the form of linear matrix inequalities, which include the existing synchronous mixed H ∞ and passivity-based controllers as a special case. A significant difference from the existing results is that the value of the developed dwell-time-dependent Lyapunov function does not necessarily meet the non-increasing condition at the switching instant. In addition, it has been shown that the obtained results are also suitable for the case where the value of dwell-time-dependent Lyapunov function is strictly decreasing both at the switching instant and during the unmatched interval. Finally, a water-quality system and a continuous stirred tank reactor are employed to substantiate the potential and effectiveness of the developed results.